Financial inclusion for sustainable agriculture: Pathways among smallholder women farmers in rural Zambia - Gershom Endelani Mwalupaso; Xianhui Geng; Salman Ibn Yasin (PLoS ONE, 2025)
Rural women constitute a substantial portion of the global agricultural workforce yet remain marginalized in access to credit, agricultural inputs, and information. This persistent exclusion not only constrains their productivity but also undermines efforts to build resilient and sustainable food systems. As climate variability increasingly threatens smallholder farming, climate-smart agriculture (CSA) has gained prominence as a viable approach to enhance agricultural sustainability, productivity, and adaptation. However, adoption of CSA among smallholder women farmers remains patchy and elusive. In response, development actors have promoted village savings and loan associations (VSLAs) to enhance women’s access to financial services. Yet, whether—and through which mechanisms—women participation (WP) in VSLAs influences CSA adoption remains insufficiently understood. To address this knowledge gap, the study investigates the pathways through which WP in VSLAs influences CSA adoption, considering the mediating role of agricultural informatization (AgI). A cross-sectional, mixed-methods design was employed, using a multistage random sampling technique to survey 436 smallholder women farmers in rural Zambia. Quantitative data were collected through a pre-tested structured questionnaire, supplemented by qualitative data from key informant interviews. Mediation analysis, using the Sobel test and bias-corrected bootstrapping, was applied to estimate pathways, while propensity score matching (PSM) was used to check the robustness of results. Findings reveal that WP in VSLAs significantly boosts CSA adoption, with a total effect size of 47%. Notably, 66% of this effect is mediated through AgI, underscoring the critical role of digital tools in supporting agricultural processes and translating financial inclusion into sustainable farming outcomes. By advancing policy discourse on the intersection of financial inclusion, gender equality, and sustainable agriculture, this research provides valuable insights for informing inclusive agricultural policies and development programs aimed at shaping future interventions in global agricultural development.